PERANCANGAN SISTEM INFORMASI PELAYANAN PASIEN BERBASIS WEB PADA PRAKTIK MANDIRI BIDAN LIA YULIANINGSIH - Ely Nuryani; Huswatun Hasanah; Dadang Amiruddin; Sherlita Saputri Pratama (LPPM Unbaja, 2024)
Midwife Lia Yulianingsih Independent Practice is a place to provide services in the health sector such as serving examinations for pregnant women, examination of children and toddlers, providing child immunizations, injecting birth control, and assisting the delivery process. The patient service process is still relatively conventional and less effective and efficient in the process of patient registration, reporting, and data collection. Management of patient examination history data is also still carried out manually. Based on this, solutions are needed in overcoming existing problems, it is necessary to have a computerized system so that information runs quickly and accurately. The method is the waterfall with Unified Modelling Language (UML). The programming language used is PHP with a Mysql database. The purpose is to determine the proposed system, design and implement a web-based patient service information system at the Independent Practice of Midwife Lia Yulianingsih. The results obtained are midwives and assistant midwives will be more effective and efficient in registering patients and recording patient examination data, providing ease of searching patient data and previous patient history examination data, thus helping all related processes become faster, facilitating the work of officers in making patient visit reports and income reports more quickly and accurately